The Role of Karang Taruna in the Development of Youth Groups in Bendungan Village, Kulon Progo Regency - Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The background of this research is as a form of a movement to break from delinquency and crime in the younger generation of Kuncen Hamlet, Bendungan Village, such as starting to try to consume drugs and alcohol, so that this problem is very worrying for their future survival and disturbing the surrounding environment. The formulation of the problem in this research is What is the Role of Youth Organizations in Developing Youth Groups in Kuncen Hamlet, Bendungan Village, Kulon Progo Regency. could harm him. This research use desciptive qualitative approach. The subjects in this study were youth organizations, youth, community leaders in the village of Pematang Seleng, by collecting observational data. Based on the results of the study, it showed that there were problems that occurred in the youth generation of Kuncen Hamlet, Bendungan Village, Wates sub-district.